Laparoscopic sacrocolpopexy: A comprehensive literature review on current practice. (February 2020) - Gluck, Ohad; Blaganje, Mija; Veit-Rubin, Nikolaus; Phillips, Christian; Deprest, Jan; O'reilly, Barry; But, Igor; Moore, Robert; Jeffery, Stephen; Haddad, Jorge Milhem; Deval, Bruno
Abstract: Sacrocolpopexy is considered the preferred treatment for vaginal vault. However, numerous technical variants are being practiced. We aimed to summarize the recent literature in relation to technical aspects of laparoscopic sacrocolpopexy (LSC). We focused on surgical technique, mesh type, concomitant surgeries, and training aspects. We performed 2 independent literature searches in Medline, Scopus, the Cochrane library, and Embase electronic databases including the keywords: 'sacrocolpopexy', 'sacral colpopexy' and 'promontofixation'. Full text English-language studies of human patients, who underwent LSC, published from January 1, 2008 to February 26, 2019, were included. Levels of evidence using the modified Oxford grading system were assessed in order to establish a report of the available literature of highest level of evidence. Initially, 953 articles were identified. After excluding duplicates and abstracts screening, 35 articles were included. Vaginal fixation of the mesh can be performed with barbed or non-barbed (level 1), absorbable or non-absorbable sutures (level 2). Fixation of the mesh to the promontory can be performed with non-absorbable sutures or non-absorbable tackers (level 2). The current literature supports using type 1 mesh (level 2). Ventral mesh rectopexy can safely be performed with LSC while concurrent posterior repair has no additional benefit (level 2). There is no consensus regarding the preferred type of hysterectomy or the benefit of an additional anti urinary incontinence procedure. A structured learning program, as well as the number of procedures needed in order to be qualified for performing LSC is yet to be established. There are numerous variants for performing LSC. For many of its technical aspects there is little consensus.